The determinants of employee's job performance at Politeknik Ungku Omar, Ipoh / Farah Syamimi Noordin - Noordin, Farah Syamimi (2014)
Recently, researchers have come to accept that performance is best defined as being a function of employees' workplace behaviors in the challenges world (Dunlop & Lee, 2004). This study is to identify the determinants of employee's job performance in Politeknik Ungku Omar, Ipoh (PUO). Throughout the study, it involves with three factors namely selection, training and compensation and benefits. The data are gained through survey which conducted about two months with targeted of 100 samples. All of the factors have a significant relationship towards employee's job performance. One of the objectives of this study is to identify the relationships between selection, training and compensation and benefits towards employee's job performance, therefore the Pearson correlation coefficient analysis is used. Based on the analysis, training shows a strong relationship towards employee's job performance.